QUALITY OF DIGITAL POPULATION ADMINISTRATION SERVICES AT PARADEWI IN BANDARASRI VILLAGE, MOJOKERTO REGENCY - Firdausiva, Wisda Fawwas; Choiriyah , Ilmi Usrotin (Proceeding of International Conference on Social Science and Humanity, 2025)
Objective: This study explores the quality of digital population administration services through the ParaDewi application in Bandarasri Village, Mojokerto Regency. The main focus of this study is to assess the impact of ParaDewi's implementation on the effectiveness and efficiency of administration, particularly in the management of documents such as Family Cards, electronic ID cards, and birth certificates. Method: The method used in this study is descriptive qualitative, with data collection conducted through interviews with village officials and the community as service users. For data analysis, the SERVQUAL framework was used to measure service quality based on five dimensions, namely physical evidence, reliability, responsiveness, assurance, and empathy. Results: The findings of this study indicate that ParaDewi has succeeded in improving the quality of population administration services. In terms of physical evidence, the availability of computers, internet access, and digital document systems supports the smooth running of the service process. Reliability is evident in the ability of village officials to provide services on time and in accordance with procedures. Responsiveness is seen in the willingness of officers to help the community, especially those who are not familiar with digital technology. The assurance dimension can be seen in the professional, transparent, and friendly attitude shown by officers, which in turn increases public trust in digital services. Meanwhile, empathy is an important element because officers try to understand the needs of citizens and adjust services to the existing social context. Novelty: This application is an innovation in technology-based public services, aimed at facilitating the community in handling population documents.